2016
DOI: 10.5465/amj.2014.0840
|View full text |Cite
|
Sign up to set email alerts
|

Come Aboard! Exploring the Effects of Directorships in the Executive Labor Market

Abstract: In this study, we examine the following question: What do executives gain from serving on boards? We propose that board service benefits non-CEO-level executives in the executive labor market by acting as a certification mechanism and by providing access to unique knowledge, skills, and connections. We argue that non-CEO executives who gain directorships will be more likely to be promoted to CEO both inside and outside their home firm, will be more likely to be promoted internally, and will receive higher pay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 126 publications
0
46
0
Order By: Relevance
“…Outside directorships are external social network ties that connect top executives to boards outside their organization through service on these boards (Geletkanycz & Hambrick, 1997; Haunschild, 1993). Directorships are positions open to and held by multiple types of executives, including CEOs and non-CEO TMT members (e.g., Boivie et al, 2016; Boivie et al, 2012; Boyd, Haynes, & Zona, 2011; Geletkanycz & Boyd, 2011).…”
Section: Tmt Boundary Spanning and Firm Performance: The Social Netwomentioning
confidence: 99%
See 3 more Smart Citations
“…Outside directorships are external social network ties that connect top executives to boards outside their organization through service on these boards (Geletkanycz & Hambrick, 1997; Haunschild, 1993). Directorships are positions open to and held by multiple types of executives, including CEOs and non-CEO TMT members (e.g., Boivie et al, 2016; Boivie et al, 2012; Boyd, Haynes, & Zona, 2011; Geletkanycz & Boyd, 2011).…”
Section: Tmt Boundary Spanning and Firm Performance: The Social Netwomentioning
confidence: 99%
“…Although we expect TMT cohesion to moderate the TMT boundary spanning–firm performance relationship generally, in part because it mitigates the challenges of outside directorships put forth by the agency perspective, evidence suggests that these challenges of opportunism are likely to be particularly applicable to non-CEO TMT members. For example, Boivie and colleagues (2016) have shown that outside directorships provide a signal that a non-CEO TMT member is a viable CEO successor and worthy of promotion either internally or externally. They argue that outside directorships are thus attractive to non-CEO TMT members because of these increased benefits in the executive labor market, despite the extra demands on their time and attention.…”
Section: Tmt Boundary Spanning and Firm Performance: The Social Netwomentioning
confidence: 99%
See 2 more Smart Citations
“…Given its key role in the model, it is worthwhile to consider the nature of the personal benefits DL have in mind in the context of what motivates directors. Directors receive direct compensation and other benefits from serving on boards (Adams et al 2010;Boivie et al 2016;Mace 1986;Perry and Peyer 2005;Useem and Karabel 1986). Direct compensation is comprised of both equity and cash.…”
mentioning
confidence: 99%